2008
DOI: 10.3168/jds.2007-0705
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cow Factors on the Incidence of Clinical Mastitis in Dairy Cows

Abstract: Many cow-specific risk factors for clinical mastitis (CM) are known. Other studies have analyzed these risk factors separately or only analyzed a limited number of risk factors simultaneously. The goal of this study was to determine the influence of cow factors on the incidence rate of CM (IRCM) with all cow factors in one multivariate model. Also, using a similar approach, the probability of whether a CM case is caused by grampositive or gram-negative pathogens was calculated. Data were used from 274 Dutch da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
55
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 32 publications
14
55
1
Order By: Relevance
“…The increased risk of CM in parity is consistent with the results of several authors (8,(12)(13)(14)(15). Steeneveld et al (16) reported that the incidence rate of CM in the first 10 days of lactation was higher in heifers than in multiparous cows. However, after 10 days of lactation, it was higher in multiparous cows than in heifers.…”
Section: Discussionsupporting
confidence: 81%
“…The increased risk of CM in parity is consistent with the results of several authors (8,(12)(13)(14)(15). Steeneveld et al (16) reported that the incidence rate of CM in the first 10 days of lactation was higher in heifers than in multiparous cows. However, after 10 days of lactation, it was higher in multiparous cows than in heifers.…”
Section: Discussionsupporting
confidence: 81%
“…In agreement with our results, another report showed for both heifers and multiparous cows, season of the year was significantly associated with the incidence of clinical mastitis (Steeneveld et al 2008). Olde Riekerink (2007) also showed that season was associated with bulk milk somatic cell count, individual cow somatic cell count, and incidence rate of clinical mastitis.…”
Section: Discussionsupporting
confidence: 92%
“…In an individual herd, cow factors are responsible for the difference among cows with clinical mastitis (Steeneveld et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Subclinical mastitis (SCLM) in heifers is an indicator for udder health and has been associated with production losses, higher probabilities of clinical mastitis, and culling (De Vliegher et al, 2005;Whist et al, 2007;Steeneveld et al, 2008). As a result, SCLM causes economic losses for the farmer (Huijps et al, 2009).…”
Section: Introductionmentioning
confidence: 99%